2000
DOI: 10.1046/j.1523-536x.2000.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Routine Use of External Cephalic Version in Three Hospitals

Abstract: External cephalic version is effective in reducing the number of cesarean deliveries in term breech infants in different obstetric settings, with no major neonatal adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2
12

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 19 publications
1
19
2
12
Order By: Relevance
“…Previously reported complications associated with ECV in women with prior cesarean delivery include transient fetal heart abnormalities, vaginal bleeding, and the need for emergency cesarean delivery. [7][8][9][10][11][12][13] No cases of uterine rupture have been reported to date, but in the present study, two women had scar dehiscence, which was noted during cesarean delivery performed for fetal distress in labor. These incidents of scar dehiscence could be related to factors during labor rather than ECV, because scar dehiscence occurred 10 days after the performance of ECV.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Previously reported complications associated with ECV in women with prior cesarean delivery include transient fetal heart abnormalities, vaginal bleeding, and the need for emergency cesarean delivery. [7][8][9][10][11][12][13] No cases of uterine rupture have been reported to date, but in the present study, two women had scar dehiscence, which was noted during cesarean delivery performed for fetal distress in labor. These incidents of scar dehiscence could be related to factors during labor rather than ECV, because scar dehiscence occurred 10 days after the performance of ECV.…”
Section: Discussioncontrasting
confidence: 44%
“…This results in a reduced threshold indicating cesarean delivery leading to an increase in emergency cesarean rates. Since 1991, when Flamm et al 6 reported a success rate of 82% for ECV in 56 women with a previous cesarean delivery, with no serious complications to the mother and fetus, seven observational studies [7][8][9][10][11][12][13] have been conducted ( Table 4). The pooled data from these studies [6][7][8][9][10][11][12][13] including 430 women with previous cesarean delivery who underwent ECV indicate an overall success rate of 76% (n=327) and no major complications to the mother and infant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These often concern unusual and rare complications. Such a complication is the version-related femur fracture in one of the analyzed studies (25). Another reported case relates to a cervical spinal cord transection possibly caused by a version procedure (93).…”
Section: Discussionmentioning
confidence: 99%
“…While the overall complication rate associated with ECV is low, [3][4][5][6][7] ECV is not without potential complications, which range from relatively minor events such as transient changes in fetal heart-rate patterns or ruptured membranes, through to rare but serious adverse outcomes including placental abruption and feto-maternal transfusion, [3][4][5][6][7][8][9][10][11] fetal distress requiring emergency caesarean section, [3][4][5][6] cord prolapse, 5,6 fracture of fetal bones, 5,12 and fetal death. 4,[13][14][15] Case reports of uterine torsion with associated fetal bradycardia, 16 fetal recto-vaginal tear requiring colostomy 17 and a fetal spinal cord transection believed to be secondary to a successful ECV exist.…”
Section: Introductionmentioning
confidence: 99%